Pyogenic granuloma: Clinicopathological and treatment scenario in Rajshahi Medical College Hospital (Central Medical College Journal, 2023)
Background: Oral pyogenic granuloma is a soft-tissue lesion of the oral mucosa. This lesion has a tendency to recur after surgical excision.Materials and Methods: A total of 35 patients underwent surgical excision of pyogenic granuloma in the period from January 2019 to June 2022. Two surgical techniques were used to remove pyogenic granuloma: simple excision with root planing and modified excision with deep curettage.Results: Females (54%) were slightly more predominant than males (46%). The upper and lower jaws were almost equally affected by the lesion with more predilection toward the posterior region. The size of the lesion ranged from 0.5 to 3 cm in diameter with slow-growing rate. Rural residents were more affected (57%) than urban people. The lesion appears clinically as a small red mass with sessile base, and these clinical features were similar in pregnant and nonpregnant women. The recurrence rate was 14.8% and seen only in patients treated by simple excision. Histopathological feature was consistent with inflammatory hyperplastic lesion, and there was no radiographic evidence of bone resorption associated with the lesion.Conclusion: Modified excision with deep curettage prevents the recurrence of the lesion after 1-year follow-up.Central Medical College Journal Vol 6 No 1 January 2022 Page: 39-43